Engineering a vascular endothelial growth factor 165-binding heparan sulfate for vascular therapy - Wang, Chunming (2016)
The therapeutic use of VEGF165 to stimulate blood vessel formation for the treatment of peripheral arterial disease or cardiovascular-related disease has met with limited success. Here we describe an affinity-isolated heparan sulfate glycotherapeutic (HS7+ve) that binds to, and enhances the bioactivity of, VEGF165. Application of HS7+ve complexed with VEGF165 results in enhanced VEGF165–VEGFR2 interaction, prolonged downstream pErk1/2 signalling, and increased cell proliferation and tube formation in HUVECs, compared with VEGF165 alone. The pro-angiogenic potential of HS7+ve was further assessed in vivo using the chick embryo chorioallantoic membrane (CAM) assay. Exogenous dosing with HS7+ve alone significantly enhanced the formation of new blood vessels with potencies comparable to VEGF165. These results demonstrate the potential for vascular therapy of glycotherapeutic agents targeted at augmenting the bioactivity of VEGF165.